P183 Transcranial direct current stimulation improves sleep quality. Issue 3 (March 2017) - Ruggiero, F.; Nigro, M.; Ferrucci, R.; Vergari, M.; Ariodante, A.; Monti, A.; Cortese, F.; Bocci, T.; Barbieri, S.; Priori, A.
Abstract : Introduction: Sleep disturbance has been recognized as a common and significant complication linked to decreased quality of life in patients with neuropsychiatric disease. Currently, pharmacological therapy is the most common treatment for sleep disturbance, although benefits tend to be limited. Objective: We assessed whether transcranial direct current stimulation (tDCS) improves sleep quality in patients with neurological and psychiatric diseases. Materials & methods: 26 neuropsychiatric patients (age 19–86, n = 2 stroke, n = 4 dysphagia, n = 3 pain, n = 8 hereditary spastic paraparesis, n = 4 Parkinson's disease, n = 2 aphasia, n = 3 depression) underwent tDCS treatment. tDCS montage was different for each pathology. The intensity of stimulation was set at 2 mA and delivered for 20 min for 5 consecutive days. The Pittsburgh Sleep Quality Index (PSQI) (Buysse, 1989 ) was used to assess sleep quality at baseline (T0) and after the tDCS treatment (T1). Results: One way ANOVA analysis showed that anodal tDCS improved PSQI total score by 13% [(mean ± SD) T0: 6.3 ± 4 vs T1: 5 ± 3.6; p = 0.004] and PSQI sub-item scores subjective quality of sleep by 22% (T0: 1.1 ± 0.7 vs T1: 0.92 ± 0.68; p = 0.016) and habitual sleep efficiency by 17% (T0: 0.31 ± 0.67 vs T1: 0.04 ± 0.19 p = 0.031). No differences were found between pathology. Conclusion: Despite the small sample size and different tDCS montages, data from our observational study showed that anodal tDCS for five days improved sleep quality and efficiency. tDCS could be a non-invasive and valuable new tool for managing sleep disorders.